2022
DOI: 10.22541/au.164873348.84448275/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Unpredictable Sound Stress Model Causes Migraine-Like Behaviors in Mice With Sexual Dimorphism

Abstract: Background and purpose Migraine represents one of the major causes of disability worldwide and is more prevalent in women, it is also related to anxiety symptoms. Stress is a frequently reported trigger in migraine patients, such as sound stress, but the underlying mechanisms are not fully understood. However, it is known that patients with migraine have higher levels of plasma inflammatory cytokines and calcitonin gene-related peptide (CGRP). Stress mediated by unpredictable sound is already used as a model o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 52 publications
(102 reference statements)
0
2
0
Order By: Relevance
“…Further, only females exhibited anxiety and increased levels of IL-6. Female-specific increases in IL-6 levels have been observed in mouse models of TMD and stress ( 91, 92 ), suggesting it may represent a marker of sexual dimorphism. In previous work, we also found that the joint effects of COMT inhibition and stress on sexual dimorphism in pain and depressive behavior were linked to female-specific changes in the expression of brain derived neurotrophic factor (BDNF) in the spinal cord and hippocampus ( 93 ).…”
Section: Discussionmentioning
confidence: 99%
“…Further, only females exhibited anxiety and increased levels of IL-6. Female-specific increases in IL-6 levels have been observed in mouse models of TMD and stress ( 91, 92 ), suggesting it may represent a marker of sexual dimorphism. In previous work, we also found that the joint effects of COMT inhibition and stress on sexual dimorphism in pain and depressive behavior were linked to female-specific changes in the expression of brain derived neurotrophic factor (BDNF) in the spinal cord and hippocampus ( 93 ).…”
Section: Discussionmentioning
confidence: 99%
“…Also, the International Society for Advancement of Cytometry Marylou Ingram Scholar (ISAC). This paper was posted on a preprint server Authorea https://doi.org/10.22541/au.164873348.84448275/v1 ( Viero et al, 2022b ).…”
mentioning
confidence: 99%